2012
DOI: 10.1055/s-0032-1316558
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic Acid as Efficient and Eco-Friendly Catalyst for the One-Pot, Three-Component Synthesis of α-Aminophosphonates under Solvent-Free Conditions

Abstract: A simple, mild, and efficient one-pot, three-component synthetic method has been developed for the preparation of α-aminophosphonates using phenylboronic acid as catalyst under solventfree conditions at 50°C. The process involves the reaction of carbonyl compounds (aldehydes or ketones) with benzylamine and dimethyl phosphite. A wide range of carbonyl compounds are compatible with this reaction, producing tertiary and quaternary αaminophosphonates in moderated to excellent yields in short time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…An efficient method was developed for the preparation of α-aminophosphonates ( 26 ), which involved applying phenylboronic acid as the catalyst under solvent-free conditions at 50 °C ( Scheme 21 ) [ 44 ].…”
Section: Kabachnik–fields Reactions With Dialkyl Phosphites Alkyl H -Phosphinates and Secondary Phosphine Oxidesmentioning
confidence: 99%
“…An efficient method was developed for the preparation of α-aminophosphonates ( 26 ), which involved applying phenylboronic acid as the catalyst under solvent-free conditions at 50 °C ( Scheme 21 ) [ 44 ].…”
Section: Kabachnik–fields Reactions With Dialkyl Phosphites Alkyl H -Phosphinates and Secondary Phosphine Oxidesmentioning
confidence: 99%
“…[37] In 2012, Mario Ordóñez et al developed a one-pot, three-component synthesis of α-amino phosphonates under solvent-free conditions using phenylboronic acid as an efficient and eco-friendly catalyst. [38] In 2014, the same group reported phenyl phosphonic acid as an efficient and recyclable catalyst in the synthesis of α-amino phosphonates under solvent-free conditions. [39] In 2017, Keglevich et al reported a microwave-assisted Pudovik reaction for the synthesis of α-aryl-α-amino phosphonates and α-aryl-αamino phosphine oxides.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Mario Ordóñez et al . developed a one‐pot, three‐component synthesis of α‐amino phosphonates under solvent‐free conditions using phenylboronic acid as an efficient and eco‐friendly catalyst [38] . In 2014, the same group reported phenyl phosphonic acid as an efficient and recyclable catalyst in the synthesis of α‐amino phosphonates under solvent‐free conditions [39] .…”
Section: Introductionmentioning
confidence: 99%
“…According to the approach of Kirilov and Petrova, carbanions generated from phosphonates were added to the CvN double bond of imines. [20][21][22][23][24][25][26] Last but not least, catalytic hydrogenation of β-iminophosphonates [27][28][29][30] and β-nitrophosphonates [31][32][33] may also be a suitable method for the preparation of β-aminophosphonates. α,β-Diaminophosphonates were also described as promising new targets.…”
Section: Introductionmentioning
confidence: 99%